THE EFFECT OF PALLIATIVE CARE ON THE QUALITY OF LIFE OF HIV/AIDS PATIENTS UNDERGOING ANTIRETROVIRAL THERAPY (SYSTEMATIC REVIEW) - Fauzi, Achmad; Riswan, Nabilla Adinda Putri; Rabino, Michael; Wijaya, Mustika Rachma; Tatuhey, Putry; Mulyani, Septi Dwi; Widya, Anggraini Kusuma; Saogo, Lasma Angelita; Dewi, Intan Titania Frychillia; Ababil, Ridho Ahmad (Fakultas Ilmu Kesehatan, Universitas Ibn Khaldun, Bogor, 2026)
The whole world is still facing the same problem: HIV/AIDS, to identify factors that affect the quality of life of HIV and AIDS patients In addition, including describing the quality of life of people living with HIV, analyzing the quality of life of people living with HIV/AIDS, and assessing the quality of life of people living with HIV/AIDS This research method is in the form of a Systematic Review, starting with an online database search including ProQuest, Chocrane Library, and PubMed. With the search keywords HIV/AIDS AND Antiretroviral Therapy AND Quality Of Life. Based on several studies mentioned, different results were obtained for each variable. The factors measured in different tests have different levels of influence and significance on the results. The conclusion that can be drawn based on a literature review of several journals mentioned is that social support is the factor that has the greatest influence on the quality of life of PLWHA Followed by the element of compliance when taking medication These two factors make the role of the family very important in improving the quality of life of people with HIV/AIDS.